Classification of urban soils in russian soil classification system and international classification of soils - B. F. Aparin; Ye. Yu. Sukhacheva (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Based on the example of St-Petersburg a genetic diversity of natural, human-transformed and anthropogenic soils has been thoroughly studied at the urbanized territory of this city. Under consideration are changes in components of the soil cover caused by the human activities along with regularities in the soil cover formation that has being developed for several centuries from the beginning of the 18th century. It is also shown how changed the initial profile of natural soils accompanying the urbanization process with special emphasis on peculiar features of the soil formation at the urbanized territory. Among a great variety of surface bodies at this territory the soils were found out, the definition of which is given in Russian soil classification system and WRB. The principles for classifying the urban soils are considered. The distinct morphological features of an introduced horizon are determined to give the comprehensive characteristics of human-transformed soils. Under discussion is the concept of “introduced horizon” composing of the human-modified material from the humus or organogenic horizons of natural soils and having the lower sharply expressed boundary with the bedrock. In Russian soil classification system it would be advisable to use a new order of “introduced soils” within the trunk of synlithogenic soils along with stratozems, volcanic, weakly developed and alluvial soils. In WRB it would be also possible to identify a new reference group of soils including the soils with the introduced horizon and underlying by any mineral substratum of natural or anthropogenic origin.